Biosorption Method of Removal of Nickel(II) Accumulated with Nasturtium officinale in Water - Kara, Yesim (Asian Journal of Chemistry, 2013)
In present study, Nasturtium officinale has been used as a plant. The plant has been collected from the campus of Dicle University of Turkey. Air roots of the plant with the same number and morphology of leaf has been chosen. For biosorption of Ni2+ metal ions by Nasturtium officinale the solutions were prepared as 0.1, 0.3, 0.5, 1.0, 2.0, 3.0, 4.0 and 5.0 ppm, respectively. It was seen that plants with low Ni2+ concentration medium biosorped all heavy metals in medium with passage of time, plants started deforming from their roots. Though some plants grown at 4 ppm biosorped less than 5 ppm it was exceptional and couldn't be generalized.